2023
DOI: 10.55606/jpikes.v3i1.1662
|View full text |Cite
|
Sign up to set email alerts
|

Penyuluhan Kepada Remaja Putri Untuk Meningkatan Pengetahuan Dan Sikap Terhadap Konsumsi Tablet Tambah Darah

Muhammad Irwan Setiawan,
Lenny Indah Cahyani,
Fajar Adi Mulya
et al.

Abstract: Iron deficiency anemia is a health problem experienced by many adolescent girl. Iron deficiency anemia will affect the learning progress of adolescent girls. Regularly consuming Blood Supplement Tablets (BST) can prevent and control iron deficiency anemia. The low coverage of BST consumption in the South Banjarbaru Public Health Center working area only reached 3.79%. Behavior change is implemented with counseling. Behavior change can be achieved by the intervention of behavioral predisposing factors. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…How does the health examination of prospective brides as a form of family concern in guarding the quality of PUS affect the incidence of stunting in the family, does the provision of vitamin A to under-fives also have an influence on stunting cases and the intake of blood supplement tablets in pregnant women affect the incidence of stunting in the babies they give birth to. Based on research by Setiawan et al (2023), suggested that giving blood supplement pills to pregnant women has a significant effect on stunting. Therefore, a study is needed to prove or validate previous research related to stunting.…”
Section: Introductionmentioning
confidence: 99%
“…How does the health examination of prospective brides as a form of family concern in guarding the quality of PUS affect the incidence of stunting in the family, does the provision of vitamin A to under-fives also have an influence on stunting cases and the intake of blood supplement tablets in pregnant women affect the incidence of stunting in the babies they give birth to. Based on research by Setiawan et al (2023), suggested that giving blood supplement pills to pregnant women has a significant effect on stunting. Therefore, a study is needed to prove or validate previous research related to stunting.…”
Section: Introductionmentioning
confidence: 99%